2018
DOI: 10.1016/j.archoralbio.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Third molar agenesis as a potential marker for craniofacial deformities

Abstract: The identification of clinical patterns of tooth agenesis in individuals born with craniofacial deformities may be a useful tool for risk determination of these defects. We hypothesize that specific craniofacial deformities are associated with third molar agenesis. Objective: The aim of this study was to identify if third molar agenesis could have a relation with other craniofacial structure alterations, such as cleft lip and palate, skeletal malocclusion, or specific growth patterns in humans. Design: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…We and others have suggested that dental abnormalities outside the cleft area could serve as clinical markers for the definition of sub-phenotypes, suggesting a genetic background for such conditions (Aspinall et al 2014;Fernandez et al 2018;Küchler et al 2011;Letra et al 2007;Menezes et al 2008;Yildirim et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…We and others have suggested that dental abnormalities outside the cleft area could serve as clinical markers for the definition of sub-phenotypes, suggesting a genetic background for such conditions (Aspinall et al 2014;Fernandez et al 2018;Küchler et al 2011;Letra et al 2007;Menezes et al 2008;Yildirim et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…También se ha reportado asociación entre agenesia del tercer molar con fisura palatina y/o labio fisurado, donde Fernandez et al (2018), reportaron una alta prevalencia del 55 % en personas con agenesia de los terceros molares y nacidos con labio fisurado y/o fisura palatina, por lo que plantea que esto podría tener un alto valor predictivo de riesgo para desarrollar hendiduras.…”
Section: Asociación Con Otras Patologías Y Síndromesunclassified
“…Ahhoz, hogy a harmadik nagyőrlő csírahiánya teljes bizonyossággal kórismézhető legyen, a csonton belüli mineralizálódása olyan szintet kell, hogy elérjen, hogy röntgenárnyék alapján ez lehetséges legyen. Későn fejlődő fogról van szó, eseteink egy része pedig 12 év alatti, amikor ez a kórisme kétséges [26,27].…”
Section: Megbeszélésunclassified